ICHONOGRAPHIC: ANALYSIS OF MERAK TEMPLE IN KARANGNONGKO KLATEN - Gavin Artamevi Lorenza (Kalyanamitra: Journal of Archaeological Resource Management, 2025)
Merak Temple is one of the relics of the Mataram Kuno Kingdom located in Candi Hamlet, Karangnongko Village, Karangnongko District, Klaten Regency. Merak Temple has a variety of iconography contained in the temple building from the foot of the temple, the body of the temple, and the roof of the temple. This study aims to find out the variety of iconography in Merak Temple as a study material on the religious background and architectural characteristics of Merak Temple. The writing method used is descriptive-explanative. The results found that Merak Temple has a Hindu background with iconographic evidence that shows the characteristics of Hindu-style temples. The iconography in the Merak Temple complex shows that the temples in the complex have a Hindu background. This is evidenced by the iconography of the various ornaments attached to the temple building, namely the Ganesha statue, the Durga Mahisasura Mardini statue, the Nandi, Yoni, and the relief that tells the story of the ocean in Yoni.